2015
DOI: 10.1590/1982-0216201520313
|View full text |Cite
|
Sign up to set email alerts
|

Processamento auditivo temporal em crianças com transtorno do déficit de atenção com hiperatividade (TDAH)

Abstract: OBJETIVO:comparar os achados da avaliação comportamental do processamento auditivo temporal em crianças com e sem Transtorno do Déficit de Atenção com Hiperatividade.MÉTODOS:participaram desse estudo 30 crianças na faixa etária de 8 a 12 anos, sendo 15 do grupo controle e 15 do grupo pesquisa, com limiares audiométricos dentro dos padrões de normalidade. Como procedimentos foram realizados os testes temporais de padrão de frequência e de duração.RESULTADOS:na comparação entre o grupo controle e grupo pesquisa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
1
7
0
2
Order By: Relevance
“…For the control group, mean P3 latency was 310.59 ms ± 53.71, results that confirm other studies in children with good school performance, in which the means of P3 latency were 332.25 ms ± 34.57 msec (3) , 336 ms ± 53 ms (13) , 315 ms ± 35.7 ms (20) , 320 ms ± 32.80 ms (21) , 316 ms ± 32.2 ms (22) , 305.71 ms ± 4.76 ms (23) . When comparing P3 latency values between the groups, we found that the mean of the study group (417.24 ms) was significantly higher in relation to the control group (310.58 ms).…”
Section: Discussionsupporting
confidence: 87%
“…For the control group, mean P3 latency was 310.59 ms ± 53.71, results that confirm other studies in children with good school performance, in which the means of P3 latency were 332.25 ms ± 34.57 msec (3) , 336 ms ± 53 ms (13) , 315 ms ± 35.7 ms (20) , 320 ms ± 32.80 ms (21) , 316 ms ± 32.2 ms (22) , 305.71 ms ± 4.76 ms (23) . When comparing P3 latency values between the groups, we found that the mean of the study group (417.24 ms) was significantly higher in relation to the control group (310.58 ms).…”
Section: Discussionsupporting
confidence: 87%
“…Encontram-se na literatura compulsada, outras pesquisas, com a população pediátrica, em que são referidos valores de latência e amplitude dos componentes do PEALL em crianças audiologicamente normais 5,6 e/ou crianças com patologias 3,4,26,27,28 . Entretanto, a presente pesquisa expõe uma proposta de valores referência para o registro e análise do PEALL, com estímulos verbais e fones de inserção, no equipamento Smart EP da IHS, de crianças típicas com idade entre 5 e 9 anos e 11 meses.…”
Section: Discussionunclassified
“…Ressalta-se que a confiabilidade do PEALL já foi pesquisada anteriormente 26,29 e tal procedimento traz informações relevantes sobre o processamento auditivo central dos estímulos acústicos. Além disso, este instrumento de avaliação assume um lugar de importância, tanto na prática clínica de avaliação dos distúrbios da audição, quanto das pesquisas científicas relacionadas à Eletrofisiologia da audição.…”
Section: Discussionunclassified
“…There is a recent study in which children with attention deficit hyperactivity disorder (ADHD) presented a higher amplitude of P2 wave, which suggests that these children need greater activation of generators to ensure that sites remained attentive and, consequently, could differentiate the rare stimuli from frequent stimuli 27 . In another study, the exogenous component latency P2 had late appearance in school learning disorder showing a deficit on encoding and on characterization of information received via central hearing 25 .…”
Section: Discussionmentioning
confidence: 99%